Pembuatan Pupuk Organik Cair dari Urine Kambing Jawa Randu dan Sampah Organik Rumah Tangga - Fahlevi, Agam Yogi; Purnomo, Zusuf Tri; Mulia Shitophyta, Lukhi (Rekayasa, 2021)
Waste from processed household activities that do not experience good management can cause environmental pollution. The rubbish in the form of vegetable and fruit waste still contains waste that can be further processed to be more useful. Liquid organic fertilizer is fertilizer whose basic ingredients come from animals, plants, or both that have undergone a process of fermentation and its final form is liquid. The making of liquid organic fertilizer from javanese goat urine and household organic waste with the addition of EM4 bioactivators (effective microorganisms) aims to determine the effect of fermentation time length, the effect of adding EM4 bioactivators, and the effect of adding the javanese goat urine with household organic waste compared to household organic waste without the addition of javanese goat urine to the pH, N, P, and K contents in liquid organic fertilizer. The results showed that for the analysis of pH obtained in samples of 4.5 to 8.5, while for the analysis of nitrogen, phosphorus, and potassium the best nitrogen (N) content was 2.3672% in 10 mL EM4 samples with a fermentation time of 21 days. The best phosphorus (P) content was 0.6857% in the 15 mL EM4 samples with a fermentation time of 14 days. And the best potassium (K) content was obtained at 1.0559% in the EM4 samples of 10 mL with a fermentation time of 7 days.